Identification of Astrocyte-expressed Factors That Modulate Neural Stem/Progenitor Cell Differentiation - Basam Z. Barkho; Hongjun Song; James B. Aimone; Richard D. Smrt; Tomoko Kuwabara; Kinichi Nakashima; Fred H. Gage; Xinyu Zhao (2006)
Multipotent neural stem/progenitor cells (NSPCs) can be isolated from many regions of the adult central nervous system (CNS), yet neurogenesis is restricted to the hippocampus and subventricular zone in vivo. Identification of the molecular cues that modulate NSPC fate choice is a prerequisite for their therapeutic applications. Previously, we demonstrated that primary astrocytes isolated from regions with higher neuroplasticity, such as newborn and adult hippocampus and newborn spinal cord, promoted neuronal differentiation of adult NSPCs, whereas astrocytes isolated from the nonneurogenic region of the adult spinal cord inhibited neural differentiation. To identify the factors expressed by these astrocytes that could modulate NSPC differentiation, we performed gene expression profiling analysis using Affymetrix rat genome arrays. Our results demonstrated that these astrocytes had distinct gene expression profiles. We further tested the functional effects of candidate factors that were differentially expressed in neurogenesis-promoting and -inhibiting astrocytes using in vitro NSPC differentiation assays. Our results indicated that two interleukins, IL-1β and IL-6, and a combination of factors that included these two interleukins could promote NSPC neuronal differentiation, whereas insulin-like growth factor binding protein 6 (IGFBP6) and decorin inhibited neuronal differentiation of adult NSPCs. Our results have provided further evidence to support the ongoing hypothesis that, in adult mammalian brains, astrocytes play critical roles in modulating NSPC differentiation. The finding that cytokines and chemokines expressed by astrocytes could promote NSPC neuronal differentiation may help us to understand how injuries induce neurogenesis in adult brains.